Potential of Channa striatus Bloch biscuit as health food product - Safa, Parastoo (2013)
In these days, natural products are widely consumed as supplement and alternative medicine. These products have different variety and ranging from plants to animal’s sap. Animal’s oil, extracts and by-products are some of the examples. Channa striatus (Haruan) is a carnivorous and freshwater fish using traditionally for post-operative pains in Malaysia. The aim of the current study is to introduce and evaluate different health benefits of Channa striatus biscuit as a new health product. It will be difficult for many individuals to consume the fish as medicine due to its sharp smell or taste, it has to be processed into more acceptable and ready to eat product. Having a natural base, balanced nutrients, and proper processing are the three important criteria for a healthy food that Channa striatus biscuit met them. The biscuit baked based on cookies formulation, supplemented with 25% of Channa striatus traditional extract. Proximate and biochemical analysis, microbial profile, metabolic evaluation and market survey were performed to determine different health characteristics of this new product. Proximate analysis of the biscuit was performed using semi-micro Kjeldhal method for the protein, air oven method for moisture and the Soxhlet extraction for lipid. The biscuit was contained 14.65 % protein, 18.30 % lipid, 7.5 % moisture, 0.14% fibers and 2.20 % ash. Minerals were analyzed using Atomic Absorption Spectrophotometer method and results showed that biscuit was contained 4.93 μg/g zinc, 80.60 mg/100 potassium, 51.33 mg/100 calcium, 4.27 μg/g iron, 0.51 μg/g cupper, 25.7 mg/100 magnesium, 0.10 μg/g chromium and 6.74 μg/g selenium. Amino acid and fatty acid compositions of dough and biscuit were analyzed using High Performance Liquid Chromatography and Gas Chromatography, respectively. Dough and Channa striatus biscuit were contained 17 essential amino acids which highest percentage in dough and biscuit was belonged to isolecucine acid with 4.81±0.26 and 3.60±0.41 mg/g, respectively. In regarding to fatty acid, the highest percentage in the dough and biscuit were palmitic acid and oleic acid with 33.11% and 33.50%, respectively. Three indexes of metabolic rate including body weight, urine volume, and feces mass of rats fed by different products of Channa striatus were measured and compared together. Results showed that none of different Channa striatus products had any effect on the body weight of animals. However, urine and feces outputs of animals fed by HTE based pellets 10% and 20% were significantly (p<0.05) higher than animals fed by normal pellets. Results also showed that none of fish products affect blood glucose and cholesterol concentrations of animals. In the last step market survey including taste, shape, smell, size, flavor, crispiness, price, health characteristics and overall acceptability of the product were performed using 60 member of panel in Universiti Putra Malaysia. Almost 60% of volunteers were familiar with Channa striatus but only 5% consume as regular food. Based on survey, almost everyone agreed that taste is good, biscuit is crispy enough, and it not have bad smell of raw fish. Although, it seems that baking process may reduce protein content of biscuit in comparison with pure HTE, but results showed that biscuit was still contained significant amount of essential amino and fatty acids. On the other hand, this new products, without any bacterial and fungal contamination, had no any significant effect on the metabolic performance of rats. As the conclusion it seems that Channa striatus biscuit can be considered as a new health food, but more clinical studies are required to ensure about safety and health benefits on human being.